2020
DOI: 10.3389/fmicb.2020.00800
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial Effect of Selenium Nanoparticles on Mycobacterium tuberculosis

Abstract: Tuberculosis (TB) remains the leading cause of death from a single infection agent worldwide. In recent years, the occurrence of TB cases caused by drug-resistant strains has spread, and is expected to continue to grow. Therefore, the development of new alternative treatments to the use of antibiotics is highly important. In that sense, nanotechnology can play a very relevant role, due to the unique characteristics of nanoparticles. In fact, different types of nanoparticles have already been evaluated both as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 26 publications
0
24
0
2
Order By: Relevance
“…A study by Sarwar et al (2017) showed that ZnONps form a complex with cholera toxin, compromises its structure, and stops its interaction with receptors present in the erythrocytes. Also, M. tuberculosis showed in vitro susceptibility to AgNps (Tabaran et al 2020), TiO 2 (Ramalingam et al 2019), and SeNps (Estevez et al 2020), although their mechanism of action remains unclear. AgNps loaded into Ti nanotubes showed promise against biofilm cells formed by MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Sarwar et al (2017) showed that ZnONps form a complex with cholera toxin, compromises its structure, and stops its interaction with receptors present in the erythrocytes. Also, M. tuberculosis showed in vitro susceptibility to AgNps (Tabaran et al 2020), TiO 2 (Ramalingam et al 2019), and SeNps (Estevez et al 2020), although their mechanism of action remains unclear. AgNps loaded into Ti nanotubes showed promise against biofilm cells formed by MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, the occurrence of drug-resistant TB cases become an emerging issue, which requires the development of new alternative treatments beyond the current antibiotics or novel techniques to enhance the efficiency of current antibiotics. Estevez et al found that Se NPs were able to inhibit the growth of Mtb by damaging their cell envelope integrity, which indicated a new opportunity for the use of Se NPs as antimycobacterial agents by themselves, or for the development of novel nanosystems that combine the action of these Se nanoparticles with other drugs (Estevez et al, 2020).…”
Section: Intracellular Mycobacterium Tuberculosis Clearance By Selenium Nanoparticlesmentioning
confidence: 99%
“…The current increasing existence of multi-drug resistant and extensively drug-resistant strains makes the treatment of this disease an important problem in the present and, potentially, future years [ 113 ]. Some current NPs-based approaches have been concerned about this infection and have demonstrated that M. tuberculosis show in vitro susceptibility to Ag [ 114 ], selenium (Se) [ 115 ], and TiO 2 [ 116 ] NPs, but their intracellularly anti-tuberculosis activity remains unclear. Up to date, only a work asserts that PLGA NPs loaded with a highly hydrophobic citral-derived isoniazid analogue promote antibiotic targeting into replicating extra- and intracellular M. tuberculosis bacilli [ 117 ].…”
Section: Nanoparticles and Human Infectionsmentioning
confidence: 99%